STEAM-PjBL Based Learning Activities: Strategies to Improve Environmental Awareness - Subekti Anggraini; Herwin Herwin (STEAM Journal For Elementary School Education, 2025)
STEAM-PjBL is a learning model that integrates approaches STEAM (Science, Technology, Engineering, Arts, and Mathematics) with project-based learning to solve real-world problems. This learning model theoretically has the potential to influence students' environmental awareness. Low student awareness of the environment is a problem that is still often found in the field. This study aims to determine the effect of the STEAM-PjBL learning model in improving students' environmental awareness in elementary schools. This research is an experimental research type with a Pre-Experimental Design. The research subjects were 16 sixth-grade students of SDN Jambe, Kapanewon Wonosari Gunungkidul in the 2024/2025 Academic Year. The research design was One Group Pretest-Posttest Design, namely experimental research carried out on one group. Which measured before treatment (pretest) and after treatment (posttest). Data collection techniques used observation and questionnaires with a total of 20 question items. Data analysis used descriptive and inferential analysis techniques. The results of the study showed that the hypothesis test of students' concern for the environment using the dependent t test obtained a two-sided significance value of p <0.001, meaning there was a difference in the average value of students' environmental concern attitudes before and after the use of the STEAM-PjBL learning model. From the results of the study, it can be concluded that learning using the STEAM-PjBL model has a positive influence in increasing environmental concern attitudes for students at the elementary school level.